The Prototype Carbon Fund : Addressing Challenges of Globalization - An Independent Evaluation of the World Bank's Approach to Global Programs - Kelly, Lauren; Jordan, Jeffery (World Bank, Washington, DC, 2014)
The prototype carbon fund (PCF) is a public-private partnership whose mission is to pioneer a market for project-based greenhouse gas emission reductions within the framework of the Kyoto protocol to the United Nations Framework Convention on Climate Change (UNFCCC). PCF seeks to show how project-based greenhouse gas emission reduction transactions can lower the cost of compliance with Kyoto, promote sustainable development, and mobilize new resources for Bank clients. Recognizing the global environmental benefits of emissions reductions regardless of location, Kyoto allows industrialized countries and firms to offset certain obligations through the purchase of lower-cost emission reductions (ERs) in developing and in-transition countries. This review identifies Bank comparative advantage-related issues, as well as the issues raised by competition between the Bank and International Finance Corporation (IFC) in carbon finance.